Thermally assisted high efficiency ductile machining of nanocrystalline hydroxyapatite: a numerical study - Ma, Jianfeng; Pelate, Nathan; Lei, Shuting (My University, 2013)
This study investigates the role of thermal assistance and tool geometry on ductile regime machining of a nanocrystalline (nano-HAP) bioceramic using numerical simulation. AdvantEdge FEM Version 5.9 is used to conduct the simulation of orthogonal machining of the nano-HAP material. Thermal boundary conditions are specified to approximate laser preheating of the work material. The effects of operating conditions (preheat temperature, rake angle, and edge radius) on critical depth of cut, cutting force, and thrust force are investigated. Based on the pressure-based criterion for ductile regime machining (DRM), the dependence of critical depth of cut on preheating temperature is examined. It is found that for different combinations of rake angle and edge radius, the critical depth of cut increases as thermal boundary temperature increases. In addition, it is concluded that using higher thermal boundary temperature for smaller negative or 0° rake angle, we can achieve the comparable critical depth of cut obtained by using a higher negative rake angle, which usually generates higher thrust force and consequently deteriorates the dimensional accuracy of finished parts.
Keywords: Thermally assisted machining; Ductile machining; Hydroxyapatite; FEM simulation